2003
DOI: 10.1128/aac.47.1.1-6.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profile of theEscherichia coliResponse to the Antimicrobial Insect Peptide Cecropin A

Abstract: Cationic antimicrobial peptides are believed to exert their primary activities on anionic bacterial cell membranes; however, this model does not adequately account for several important structure-activity relationships. These relationships are likely to be influenced by the bacterial response to peptide challenge. In order to characterize the genomic aspect of this response, transcription profiles were examined for Escherichia coli isolates treated with sublethal and lethal concentrations of the cationic antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 31 publications
2
53
0
2
Order By: Relevance
“…It is thought that cationic peptides might induce genomic responses in bacteria treated with AMPs, in addition to any lethal effect on the bacterial membrane. This appears to be the case, as recently demonstrated (Hong et al 2003). These authors have shown that the transcription profiles of at least 26 Escherichia coli genes change specifically and significantly after exposure to lethal and sub lethal concentrations of Cecropin A, an emblematic cationic peptide.…”
Section: Relevancy Of Amps: Is There More To Come?supporting
confidence: 61%
“…It is thought that cationic peptides might induce genomic responses in bacteria treated with AMPs, in addition to any lethal effect on the bacterial membrane. This appears to be the case, as recently demonstrated (Hong et al 2003). These authors have shown that the transcription profiles of at least 26 Escherichia coli genes change specifically and significantly after exposure to lethal and sub lethal concentrations of Cecropin A, an emblematic cationic peptide.…”
Section: Relevancy Of Amps: Is There More To Come?supporting
confidence: 61%
“…For example, results by Davies (Goh et al 2002) have shown that erythromycin-mediated transcriptional modulation occurred to the same extent in both wt and mutants defective in a variety of stress response pathways. Hu et al reached a similar conclusion when examining the transcriptional changes induced by the antibiotic cecropin in E. coli O157 (Hong et al 2003).…”
Section: Mechanismmentioning
confidence: 65%
“…These properties allow many of them to initially bind the negatively charged microbial membrane and alter its integrity, leading to cell death (9,11,12). However, a few AMPs have been shown to have additional/alternative intracellular targets besides the cytoplasmic membrane (13)(14)(15)(16)(17)(18). Interestingly, several kinds of plants and animals can synthesize a considerable number of AMPs with relatively minor sequences and structural differences among them.…”
mentioning
confidence: 99%